Evaluation of Policy Providing Lactation Rooms in Public Spaces of Palembang City (Review of Palembang City Regional Regulation Number 2 of 2014) - Dewi Ratih Anggraini; Evi Satispi; Endang Sulastri (Journal Of Social Science (JoSS), 2026)
This study aims to evaluate the policy on the provision of lactation rooms in public spaces in Palembang City, based on Regional Regulation Number 2 of 2014. The research focuses on three main aspects: (1) policy evaluation using William N. Dunn's framework, (2) program implementation effectiveness analyzed through Riant Nugroho’s “five right” model, and (3) inter-actor collaboration examined from the perspective of Ansell and Gash’s Collaborative Governance theory. The study employs a descriptive qualitative approach with a case study strategy. Data were collected through in-depth interviews, field observations, and document analysis from relevant agencies. Data analysis followed the Miles and Huberman interactive model, allowing for systematic data reduction, display, and verification. The results indicate that the implementation of the lactation room provision policy in Palembang City has not been fully effective or efficient. The availability of lactation rooms remains limited and fails to meet the technical standards outlined in Minister of Health Regulation Number 15 of 2013. Coordination among agencies is suboptimal, supervision mechanisms are not sustainable, and public participation remains low. Moreover, collaborative governance practices are still primarily administrative, lacking meaningful engagement among stakeholders. Based on these findings, the study proposes a Public Space Adaptive Collaboration Model. This model positions the government as a facilitator, the private sector as a service provider, and the community as a co-creator of policy. Such a framework is intended to enhance policy implementation, promote stakeholder participation, and ensure the sustainable provision of lactation rooms in public spaces.